Sosialisasi dan Pelatihan Penanaman 1000 Pohon Mangrove di Taman Wisata Mangrove - Irawan, I Putu Redy; Idkhan, A. Muhammad; Putra, Iswahyudi Indra; Erniyani; Raodah (JPM: Jurnal Pengabdian Masyarakat, 2025)
Damage to coastal ecosystems due to abrasion, land conversion, and environmental pollution is a serious issue that threatens the sustainability of natural resources and the livelihoods of coastal communities. One effective solution to address this problem is the planting of mangroves, which serve as natural protectors of coastlines, habitats for marine life, and carbon sinks. The Community Service Kegiatan (PKM) aims to plant 1000 mangrove trees in the Klawalu Mangrove Tourism Park, Sorong City, as part of efforts to rehabilitate the environment and strengthen community-based ecotourism. This activity is conducted in several stages, namely socialization and education for the surrounding community, mapping and analysis of land conditions, selection and planting of mangrove seedlings, as well as monitoring and evaluation of plant growth. Community participation, especially from fishermen and tourist groups, is the key to the success of this kegiatan. The results of the activity indicate that mangrove planting not only provides ecological benefits, such as reducing erosion and enhancing biodiversity, but also has socio-economic impacts by increasing tourist attraction and environment-based economic opportunities. With this kegiatan, it is hoped that public awareness of the importance of mangrove conservation will increase, and it will also have a long-term impact on the balance of coastal ecosystems. Furthermore, the success of this kegiatan can serve as a model for other regions in implementing ecotourism-based environmental rehabilitation and community empowerment.